2022
DOI: 10.3389/feart.2021.824410
|View full text |Cite
|
Sign up to set email alerts
|

Study of Water Huff-n-Puff in Low-Permeability Oil Reservoirs With Horizontal Fractures: A Case Study of Chang 6 Reservoir in Yanchang, China

Abstract: Water huff-n-puff is an effective technology to enhance oil recovery (EOR) of low-permeability reservoirs, which are usually developed with hydraulic fracturing. Fluid exchange between fractures and the matrix is the main EOR mechanism. However, the presented water huff-n-puff simulations usually assume vertical fracture morphology, while the horizontal fractures formed in shallow reservoirs are rarely reported. In this study, we first introduced the water huff-n-puff process in a low-permeability oil reservoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Steam-cycling treatment of production wells refers to the methods of intensification of inflow (MIP). During steam cycling treatments, steam is pumped into a production well for 15-20 days in a volume of 100-300 tons per 1 m of formation thickness [81]. Then the well is closed for 10-15 days to redistribute heat and countercurrent capillary displacement of oil from low-permeability interlayers (LP) into a high-permeability interlayer.…”
Section: Steam-cycling Treatment Of Production Wellsmentioning
confidence: 99%
“…Steam-cycling treatment of production wells refers to the methods of intensification of inflow (MIP). During steam cycling treatments, steam is pumped into a production well for 15-20 days in a volume of 100-300 tons per 1 m of formation thickness [81]. Then the well is closed for 10-15 days to redistribute heat and countercurrent capillary displacement of oil from low-permeability interlayers (LP) into a high-permeability interlayer.…”
Section: Steam-cycling Treatment Of Production Wellsmentioning
confidence: 99%
“…27 Meng et al proposed that capillary pressure and relative permeability are the most important parameters affecting the effect of water injection huff-npuff. 28,29 During water huff-n-puff in tight reservoirs, researchers found a nonflowing thin film on the solid−liquid wall surface in the pore-throats of the matrix and studied it. Rao et al analyzed the influence of the water lock effect on the water huff-n-puff process of tight reservoirs by numerical simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the characteristics of tight reservoirs and oil recover mechanism of water huff-n-puff, it is found that water may affect oil recovery by gravity and capillary force during water huff-n-puff process. , Dynamic capillary force is the main reason for nonlinear flow in tight sandstone reservoirs . Meng et al proposed that capillary pressure and relative permeability are the most important parameters affecting the effect of water injection huff-n-puff. , During water huff-n-puff in tight reservoirs, researchers found a nonflowing thin film on the solid–liquid wall surface in the pore-throats of the matrix and studied it. Rao et al analyzed the influence of the water lock effect on the water huff-n-puff process of tight reservoirs by numerical simulation .…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have conducted research on WHP technology in tight oil reservoirs, including applicable conditions, oil recovery mechanisms, and influencing factors. However, the following problems still exist. (1) There are very few physical simulation experiments for oil recovery by WHP in tight oil reservoirs.…”
Section: Introductionmentioning
confidence: 99%